Assessing the relationship between employee training participation and performance in a telecommunications company - a case study on Robi Axiata - Simran, Amreen Reza (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.